Epitope mapping of the von Willebrand factor subunit distinguishes fragments present in normal and type IIA von Willebrand disease from those generated by plasmin. - Berkowitz, S D; Dent, J; Roberts, J; Fujimura, Y; Plow, E F; Titani, K; Ruggeri, Z M; Zimmerman, T S (The Journal of Clinical Investigation, 1987)
A small but consistent proportion of the von Willebrand factor (vWF) in normal plasma is composed of 189, 176, and 140 kD fragments cleaved from the 225 kD subunit. A monoclonal antibody map of vWF, based on the reactivity of individual antibodies with cyanogen bromide and tryptic fragments of known carboxy and/or amino termini, showed that in normal and IIA von Willebrand disease (vWD) plasmas the 140 kD fragment was derived from the amino-terminal region, whereas the 176 kD fragment was derived from the carboxy-terminal region of the subunit. In type IIA vWD, however, the fragments comprised a greater proportion of circulating vWF. In contrast, plasmin cleaved a 176 kD fragment from the amino terminus and a 145 kD fragment from the carboxy terminus of the subunit. Species similar to these plasmin-cleaved fragments were demonstrated in plasmas from four patients treated with fibrinolytic agents, but not in IIA vWD. Images